Valor nutricional y aceptabilidad de la canasta alimentaria pan TBC en relación con los requerimientos nutricionales de pacientes con tuberculosis-2024 - Yamashita Vasquez, Josselyn Patricia (2024)
This research aimed to evaluate the nutritional value and acceptability of the PAN TBC food basket in relation to the nutritional requirements of tuberculosis patients. An observational, prospective, and cross-sectional study was conducted at IPRESS I-4 BELLAVISTA NANAY-PUNCHANA, including 48 patients diagnosed with tuberculosis and beneficiaries of the PAN TBC basket in June 2024. The methodology included analysis of the basket's nutritional contribution, evaluation of its acceptability through a validated survey, and calculation of patients' nutritional requirements. Standardized nutritional software and statistical analysis with SPSS version 27 were used. Results showed that the PAN TBC basket provides 5018.3 kcal daily for the patient and four contacts, with a distribution of 8.86% protein, 61.46% carbohydrates, and 27.84% lipids. Satisfactory adequacy was observed in energy (79.2%) and carbohydrates (85.4%), but a critical deficiency in protein (6.2%). The actual contribution of the basket, although lower than theoretical, generally exceeded 50% of the patients' average requirements, except for protein. The basket showed a high level of acceptability, with 94% of participants rating it as high. A weak positive correlation was found between acceptability and patients' economic situation (rs = 0.330, p = 0.022), as well as between the nutritional value of the basket and nutritional requirements (rs = 0.352, p = 0.014). In conclusion, the PAN TBC food basket presents high acceptability and covers a large part of the nutritional requirements of tuberculosis patients. However, areas for improvement were identified, particularly in protein intake, suggesting the need for possible reformulation to optimize its nutritional value while maintaining its high level of acceptability.